A Novel Multiplex LAMP Assay for the Rapid and Accurate Diagnosis of Visceral Leishmaniasis Caused by Leishmania infantum from Iran - Sahar Samsami; Sahar Namavari; Saeed Ataei; Abdolmajid Ghasemian; Ava Yazdanpanah; Neda Sepahi; Gholamreza Hatam; Hossein Faramarzi; Hadi Mirzaei; Razie Ranjbar; Ali Ghanbariasad (Journal of Tropical Medicine, 2023)
Visceral leishmaniosis (VL) is one of the neglected tropical diseases despite being responsible for serious clinical symptoms, some of which lead to fatal outcomes. Thus, there is a need to apply accurate, rapid, and specific diagnostic measurements in order to control the disease and reduce the mortality rate. We aimed to develop and validate a multiplex LAMP assay for the diagnosis of VL caused by Leishmania infantum (L. infantum). Moreover, a thorough assessment was conducted to determine the effectiveness of multiplex LAMP in identifying various Leishmania species, such as Leishmania tropica (L. tropica) and Leishmania major (L. major) in comparison to Leishmania infantum (L. infantum). The diagnostic performance of the multiplex LAMP method for VL was compared to each LAMP assay, real-time polymerase chain reaction (RT-qPCR), and nested PCR technique. Two separated primers were set and used in a multiplex LAMP assay which was designed based on the ITS2 (internal transcribed spacer II) and were selected on the basis of conserved and high copy number region. Multiplex LAMP primers were designed using an online tool available at https://www.primerexplorer.jp/e. The alignment was performed using MEGA5, and the primers were further adjusted utilizing GENE Runner software. All molecular methods were tested on the serial dilution of cloned plasmid containing ITS region from standard strains of L. infantum, L. tropica, and L. major. Moreover, multiplex LAMP assay was evaluated and compared based on both standard strains and 55 clinical samples from humans as well as dogs. Various approaches were applied to interpret the multiplex LAMP reaction which deciphered a higher sensitivity when compared to the RT-qPCR for L. infantum (one copy number of plasmid, equal to 0.85 femtograms (fg) of plasmid concentration, and 0.004 parasite DNA per μL) detection while these three standard strains of Leishmania were confirmed to contain 40 DNA copies using RT-qPCR. Additionally, the multiplex LAMP detection limit was approximately equivalent to RT-qPCR for L. major and L. tropica, which included 0.342 picograms (pg) and 342 femtograms (fg) of plasmid concentration, 4 × 103 and 4 × 102 copy number of plasmid, and 17.1 and 1.71 parasite DNA per μL for L. major and L. tropica, respectively. Nested PCR exhibited a lower detection limit for L. infantum of 4 × 106 plasmid copy number compared to multiplex LAMP and RT-qPCR. Multiplex LAMP has the potential for accurate and rapid detection of infectious disease, successful treatment, and finding and monitoring asymptomatic cases, especially in low-income countries.